Effect of sodium hydroxide concentration on properties of carboxymethyl rice starch - P. Rachtanapun (2018)
Effect of sodium hydroxide (NaOH) concentrations on properties of carboxymethyl rice starch (CMSr) was investigated. Fourier transform-infrared (FTIR) spectrum confirmed that carboxymethylation took place on the starch molecules. The DS value of CMSrincreased with increasing NaOH concentrations (10-40% w/v). However, when the level of NaOH concentration reached 50%, the DS of the CMS decreased. The viscosity of CMSrdecreased with increasing NaOH concentrations. The morphology of native rice starch and CMSrwas further investigated through scanning electron microscope (SEM). The mirco-structure revealed that the morphology of CMSrgranules were more damage with increasing NaOH concentration which related with DS.